Energy intake and energy balance in male and female adolescent rowers in New Zealand - Speedy, J. (Massey University, 2023)
Background Adequate energy intake (EI) is essential for adolescent athletes to support health, performance, and growth. Rowing is a physically demanding sport where intense training begins in adolescence. Research is needed to assess whether current EI is sufficient to support healthy physiological functions and training in adolescent rowers. The aim of this study was to evaluate the energy status (energy availability (EA) or energy balance (EB)) including EI and exercise energy expenditure (EEE) of adolescent rowers in New Zealand.